2004
DOI: 10.1021/bi0356350
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Activation of the Ca-ATPase Enhances Conformational Heterogeneity between Nucleotide Binding and Phosphorylation Domains

Abstract: High-resolution crystal structures obtained in two conformations of the Ca-ATPase suggest that a large-scale rigid-body domain reorientation of approximately 50 degrees involving the nucleotide-binding (N) domain is required to permit the transfer of the gamma-phosphoryl group of ATP to Asp(351) in the phosphorylation (P) domain during coupled calcium transport. However, variability observed in the orientations of the N domain relative to the P domain in the different crystal structures of the Ca-ATPase follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
7
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
5
7
1
Order By: Relevance
“…This change was somewhat smaller in magnitude than the 30+ Å change predicted by the first X-ray crystallographic structures ( Fig. 1 A), but larger than that measured by other FRET studies [8], [9], [29], Most notably, the distance change observed here was opposite in direction compared to early crystal structure predictions [4]. The apparent decrease in FRET distance with Ca also contrasts with previous FRET studies that used reactive dyes as donors/acceptors.…”
Section: Discussioncontrasting
confidence: 90%
“…This change was somewhat smaller in magnitude than the 30+ Å change predicted by the first X-ray crystallographic structures ( Fig. 1 A), but larger than that measured by other FRET studies [8], [9], [29], Most notably, the distance change observed here was opposite in direction compared to early crystal structure predictions [4]. The apparent decrease in FRET distance with Ca also contrasts with previous FRET studies that used reactive dyes as donors/acceptors.…”
Section: Discussioncontrasting
confidence: 90%
“…Solution structures using probes bound to the N- and P-domains have been measured, and are consistent with high-resolution x-ray structures (9, 10). Coordinated motions of the actuator (A) domain are proposed to facilitate the association between the N- and P-domains necessary for phosphoenzyme formation and calcium occlusion (5).…”
supporting
confidence: 67%
“…In this model, PLB constrains the structure of the Ca-ATPase in its unphosphorylated state, so that higher calcium concentrations are necessary to overcome the kinetic barrier associated with the cooperative binding of the second calcium ion and the large scale structural rearrangement the results in an increase in the spatial separation between domain elements of the Ca-ATPase. Further, the calciumdependent reorientation of both the transmembrane helices of the Ca-ATPase and individual cytosolic domains is consistent with observed reductions in site-specific chemical cross-linking between engineered sites on the Ca-ATPase and PLB following calcium activation [45,49,54,68].…”
Section: Conformational Switching and Release Of Plb Inhibitionsupporting
confidence: 76%
“…Consistent with FTIR measurements [32], there are no large changes in the secondary structure of PLB associated with binding the CaATPase. Thus to bring sites on the Ca-ATPase known to interact with sites on PLB, it is apparent that PLB stabilizes a pre-existing conformation of Ca-ATPase, whose domains have previously been shown to undergo large amplitude motions that are critical for function [57,58,[67][68][73][74][75][76][77][78][79]. Thus, rather than extending the PLB structure to fit the crystal structure of the ATPase, a reorientation of the nucleotide binding domain of the Ca-ATPase by approximately ten degrees permits an efficient juxtaposition of the PLB structure near sites on the Ca-ATPase previously identified through covalent cross-linking methods to be proximal to one another (Fig.…”
Section: A Dynamic Model Of Ca-atpase Regulation By Plbmentioning
confidence: 99%